Estimation of stress concentration factor of plate with hole using piezoelectric actuator and finite element method - Abuzaid, Ahmed; Hrairi, Meftah; Shaik Dawood, Mohd. Sultan Ibrahim (IOP Publishing, 2017)
In this paper, the effect of piezoelectric actuators placed above a circular hole of a rectangular plate subjected to uniform uniaxial tension is studied. The core idea is to investigate the stress (compression/tension) produced by the piezoelectric actuators on the stress distribution around the hole and along the width of the host plate. For this purpose, Finite Element Analysis (FEA) was carried out through parametric study in ANSYS software. The results demonstrated that the positive electric field would decrease and change the state of the stress distribution along the width of the host plate in contrast to the negative applied electric filed which increases the stress distribution smoothly without affecting its behaviour. The results also indicated that the reduction of the stress concentration factor increases with the decrease of the ratio (D/W) for the same applied positive electric field.